2021
DOI: 10.1016/j.rmcr.2021.101397
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic approach for severe COVID-19 and immunocompromised patients. A case series

Abstract: Background COVID-19 is a potentially critical infectious disease. Inflammatory response and disease severity may vary according to immune system status. The aim of this case series is to investigate different presentation of COVID-19 in immunocompromised patients. Methods this is a single centre case series about 17 immunocompromised patients admitted to our respiratory department during the recent COVID-19 pandemic. White blood cell count, C reactive protein, interleuk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 4 publications
1
3
0
Order By: Relevance
“…11 Simioli et al found that immunocompromised adult patients are at risk of adverse outcomes from COVID-19, with a higher risk in patients having hematological malignancies. 12 Like our study, Fung and Babik reported similar manifestations of COVID-19 in immunocompromised and immunocompetent patients. 13…”
Section: Discussionsupporting
confidence: 83%
“…11 Simioli et al found that immunocompromised adult patients are at risk of adverse outcomes from COVID-19, with a higher risk in patients having hematological malignancies. 12 Like our study, Fung and Babik reported similar manifestations of COVID-19 in immunocompromised and immunocompetent patients. 13…”
Section: Discussionsupporting
confidence: 83%
“…A total of 459 people with PI and COVID-19 are described from 54 of the 68 studies [ 12 , 13 , 16 , [18] , [19] , [20] , [21] , 24 , 26 , 27 , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] , [68] , [69] , [70] , [71] ] (Table 2). These cases came from case reports as well as cohort studies with information available for individual patients.…”
Section: Resultsmentioning
confidence: 99%
“…The most important difference between immunocompromised and non-immunocompromised hosts is the increased risk of disease progression ( Fung and Babik, 2021 ). Antigen testing and nucleic acid amplification detection remain the mainstay of testing in acute illness ( Simioli et al, 2021 ).…”
Section: Clinical Manifestations and Diagnosis Of Covid-19 In Patient...mentioning
confidence: 99%